2006
DOI: 10.1111/j.1600-6143.2006.01281.x
|View full text |Cite
|
Sign up to set email alerts
|

C4d Deposition and Clearance in Cardiac Transplants Correlates With Alloantibody Levels and Rejection in Rats

Abstract: Antibody-mediated rejection of human cardiac transplants is correlated with C4d deposits and macrophage infiltrates in capillaries of endomyocardial biopsies. We produced an antibody to rat C4d to study C4d deposition and clearance in Lewis rats that were sensitized with a blood transfusion from DA rats 7, 14 or 21 days before cardiac transplantation. Cyclosporin A (CsA) immunosuppression was initiated after transplantation at a dose that inhibited graft rejection, antibody production and C4d deposition in uns… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
49
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(52 citation statements)
references
References 26 publications
3
49
0
Order By: Relevance
“…C4d deposition can occur as early as less than 3 months after heart transplantation to greater than 160 months and can be cleared fairly rapidly with appropriate therapy in patients with clinical AMR. This has been confirmed in animal studies using Lewis rats (28). C4d deposition in the nontransplanted heart has been described in less than 10% of patients with other forms of heart disease (22).…”
Section: Immunohistochemistrysupporting
confidence: 55%
“…C4d deposition can occur as early as less than 3 months after heart transplantation to greater than 160 months and can be cleared fairly rapidly with appropriate therapy in patients with clinical AMR. This has been confirmed in animal studies using Lewis rats (28). C4d deposition in the nontransplanted heart has been described in less than 10% of patients with other forms of heart disease (22).…”
Section: Immunohistochemistrysupporting
confidence: 55%
“…In the early 1990s, clinicopathologic observations led to the recognition of histopathological features of acute ABMR in kidney (3,4), followed by discovery of C4d staining (5 (8,9) or noncomplement activating DSA (10)(11)(12) (27) (32). (38).…”
Section: Abmr: An Underestimated Problem In Allografts Robert Colvin mentioning
confidence: 99%
“…5,6 Animal models have confirmed that donor-specific antibodies (DSAs) are associated with release of vWf in cardiac allografts. 7,8 When vWf is released, the end of the vWf multimer remains attached to endothelial cells, and strings of vWf interact with integrin GPIb-XI-V and GPIIb/IIIa on platelets. 9 In models of AMR, release of vWf is associated with adhesion of platelets to vascular endothelium of cardiac allografts.…”
mentioning
confidence: 99%